Pemetaan Tema, Metode, dan Kontribusi Value Engineering dalam Berbagai Sistem Teknik melalui Systematic literature review - Moh Ainul Fais; Silvana Mohamad; Dedy Kunhadi; Djaffar Sodiq; Novid Hidayat; Mohamad Tsaqif Apta Laksono (Universitas Katolik Darma Cendika, 2026)
Value Engineering (VE) has evolved from a cost-control technique into a Value Management approach integrating function, life-cycle cost, quality, sustainability, digitalization, and organizational capability. This study maps the themes, methods, and contributions of VE across engineering systems through a systematic literature review. The search generated 1,000 initial records. After deduplication, multistage screening, DOI and full-text verification, quality appraisal, and replacement of ineligible studies, a final corpus of 80 articles published in 2020–2026 was established. The articles were coded into seven themes, 21 subthemes, nine primary methods, ten integrative techniques, and ten contribution categories. Construction and infrastructure formed the largest theme (26.25%), while technical-economic case studies were the dominant method (31.25%). The most frequently reported contributions were cost efficiency (82.50%), decision quality (68.75%), and technical function or performance (55.00%). The review also identifies the growth of sustainability, BIM, automation, multi-criteria decision methods, and life-cycle costing. Major gaps concern inconsistent value metrics, the dominance of single-case studies, limited post-implementation evaluation, and uneven evidence across engineering systems. The study’s novelty lies in a quality-informed theme, method, and contribution evidence map.